2022
DOI: 10.1002/pro.4447
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trajectory of receptor binding specificity and promiscuity of the spike protein of SARS‐CoV‐2

Abstract: SARS‐CoV‐2 infects cells by attachment to its receptor—the angiotensin converting enzyme 2 (ACE2). Regardless of the wealth of structural data, little is known about the physicochemical mechanism of interactions of the viral spike (S) protein with ACE2 and how this mechanism has evolved during the pandemic. Here, we applied experimental and computational approaches to characterize the molecular interaction of S proteins from SARS‐CoV‐2 variants of concern (VOC). Data on kinetics, activation‐, and equilibrium t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(204 reference statements)
0
1
0
Order By: Relevance
“…Cardiovascular complications have been reported to be associated with increased mortality and worsening hospital outcomes [2] . The infection between SARS-Cov-2 and host cells relies on several receptors binding with Spike glycoprotein (S protein), including angiotensin-converting enzyme 2 (ACE2) [3] . Previous research demonstrated that the S protein would cause endothelial dysfunction by generating redox stress and impaired mitochondrial hemostasis, which revealed COVID-19 as a kind of vasculitis [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular complications have been reported to be associated with increased mortality and worsening hospital outcomes [2] . The infection between SARS-Cov-2 and host cells relies on several receptors binding with Spike glycoprotein (S protein), including angiotensin-converting enzyme 2 (ACE2) [3] . Previous research demonstrated that the S protein would cause endothelial dysfunction by generating redox stress and impaired mitochondrial hemostasis, which revealed COVID-19 as a kind of vasculitis [4] .…”
Section: Introductionmentioning
confidence: 99%